Prawna ochrona konkurencji - Oryński, Andrzej (Legal Protection of Competition, 2006)
As far as the protection of the competition is concerned, there are two important legal acts: the light against unfair competition act and competition and consumers protection act. The first statute contains the definition of unfair competition. Additionally, it names different kinds of unfair competition deeds and portrays the legal consequences of commission of the dee. The second statute forbids group actions which restrict competition and describes the competence of the Chairman of the Office of Competition and Consumers Protection. The Chairman has got the ability to fight the forbidden actions and control the concentration of entrepreneurs. The Chairman is issued with the competence to inflict a money penalty if an entrepreneur disobeys the rules of the statute or the Chairman's decision.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 188-193